Association Between Assisted Reproductive Technology and White Matter Injury in Premature Infants: A Case-Control Study - Huang, Xuejiao; Fu, JianHua (Frontiers in Pediatrics, 2021)
Objectives: Whether there is a link between assisted reproductive technology (ART) and brain damage in premature infants remains unclear. The aim of this study was to determine whether premature infants conceived by ART are at a greater risk of developing white matter injury (WMI), as detected by magnetic resonance imaging (MRI) or diffusion-weighted imaging (DWI) within 14 days, than those naturally conceived (NC). Methods: A retrospective case-control study was conducted on singleton premature infants with a gestational age of ≥28 weeks and <34 weeks delivered between 2017 and 2019 at Shengjing Hospital, China Medical University. This study included 638 live births that were stratified into case group (n = 218) and control group (n = 420), depending on the presence or absence of WMI. The exposure proportion of ART was compared between the case and control groups, and a logistic regression model was used to identify whether ART was an independent risk factor for WMI. Results: In the univariate analysis, the exposure proportion of ART conception was higher in cases than in controls (12.84 vs. 7.38%, p = 0.024). According to the multivariable analysis, after adjustment for other variables, the association between ART and WMI remained significant (1.82; 95% confidence interval, 1.04–3.21; P = 0.038). Conclusions: Singleton premature infants conceived by ART have a higher risk of WMI than NC infants. Given that ART is an independent risk factor for WMI in premature infants, more attention should be paid to neurodevelopmental outcomes in this group.